Implementation Of Religious Moderation Based on Socio-Cultural Values in Selorejo Village, Ngunut Sub-District, Tulungagung District - Manggala Wiriya Tantra; Gede Agus Siswadi; Dipesh Raj (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Indonesia is a country with multiple ethnicities, religions, languages, and others that make Indonesia a unique country, rich in diversity. However, on the other hand, if the diversity is not able to be managed properly, it will become a source of conflict and division, especially when it comes to religion which should be a source and a way to achieve peace, but it will become dangerous when looking at religious differences without applying the values of brotherhood, humanity and others. This research aims to reveal the implementation of religious moderation based on socio-cultural values in Selorejo Village, Ngunut District, Tulungagung Regency. The method used in this research is qualitative method with descriptive approach. The results of the research related to the implementation of religious moderation based on socio-cultural values in Selorejo Village, Ngunut District, Tulungagung Regency are that the Selorejo Village community has carried out many implementations of religious moderation, starting from carrying out religious events with socio-cultural principles, namely mutual cooperation and enjoying the happiness of every holiday of a particular religion. In addition, the values of brotherhood, tolerance, and also humanity are highly upheld for the sake of creating harmonious conditions, and maintaining unity as a national commitment.